Nasolabial cyst in pediatric age - Silva, Marta Ribeiro (2022)
Herein is described the case of a 26-month-old male observed in the Emergency Department for edema of the upper lip and left malar region with less than 24 hours of evolution and progressive worsening. No other associated complaints, previous history of trauma, or insect sting were reported. Computed tomography revealed a “left premaxillary abscess associated with ipsilateral nasogenian phlegm”. Intravenous antibiotic therapy with clarithromycin and clindamycin and systemic corticosteroid therapy with dexamethasone were started, and the boy was admitted to the Pediatric Department. He presented favorable clinical evolution, with complete resolution of inflammatory signs. At discharge, the patient remained asymptomatic and was referred to Otorhinolaryngology consultation for follow-up. Although nasolabial cysts are rare in pediatric age, this case intends to raise awareness of the condition, enabling its recognition by clinicians, and increase knowledge about its course and treatment.